OPTIMALISASI PRODUKTIVITAS KAMBING PERANAKAN ETAWAH DENGAN PEMANFAATAN LIMBAH PERTANIAN TERFERMENTASI DAN SUPLEMENTASI LIMBAH INDUSTRI - Aju Tjatur Nugroho Krisnaningsih; Waluyo Edi Susanto (Universitas Islam Kadiri, 2017)
The purpose of this research was to increase productivity Peranakan etawah (PE) goat with fermented hay corn and gamalleaves supplementation and tofu solid waste.Methods used Complete Random Design (RAL) through the test of fermented hay corn (JF) , gamal (G) , and tofu solid waste (AT). Feed Treatment consist of: (P0 = 60% JF + 40% G + 0% AT; P1 = 50% JF + 40% G + 10% AT; P2 = 40% JF + 40% G + 20% AT; P3 = 30% JF + 40% G + 30% AT).Each treatment repeated as much as 3 times.Parameters examined was feed consumption and weight gain and feed conversion of PE goat.When treatment give significant effect then followed by the Least Significant Different (LSD) Based on results of research showed that the utilization of agricultural and industrial wastegive significant different (P<0.01 ) against consumption, weight gain, feed conversion of PE goat.P2 treatment with composition 40 % fermented hay corn + 40 % gamal + 20 % tofu solid waste provide optimal results compared another feed treatment with feed consumption of 978,95 gram, body weight gain 102,15 gram and lowest feed conversion was 9,59. The Conclusions of this research wasfermented hay corn and gamalleaves supplementation and tofu solid waste can increase productivity of PE goat in terms of feed consumption, body weight gain and feed conversion.Suggested agricultural and industrial wasteutilization with 40% fermented hay corn + 40% gamal + 20% tofu solid waste to increase productivity and goats.